Islamic Religious Values in Dhukutan Traditional Ceremony as Character Education for Elementary School Students - Wati, Mila Anggar; Sumarwati, Sumarwati; Saddhono, Kundharu (el Harakah: Jurnal Budaya Islam, 2019)
This study aims to describe the values of Islamic religious character education in the cleaning process of Dhukutan village in Nglurah village, Tawangmangu sub-district. Dhukutan is a traditional ceremony of Nglurah villagers to commemorate the death of their ancestors named Kyai Menggung. This traditional ceremony is held once every seven lapan (1 lapan=35 days based on Javanese calendar). The method used to find the value of religious character education is a descriptive qualitative method. The sources of the data are the offerings related to the implementation of the Dhukutan village cleaning ceremony. The results of the study show that the religious values reflected in the Dhukutan traditional ceremony are sincere, honest, obedient, disciplined, diligent, praying, grateful, and trustworthy. Within the process of Dhukutan village cleaning ceremony, the value of religious character education is beneficial for students to be both intellectually and emotionally intelligent students. This study suggests educators, especially within Tawangmangu area, to employ the Dhukutan village cleaning ceremony as a learning tool of religious character education values for elementary students. Penelitian ini bertujuan untuk mendeskripsikan nilai pendidikan karakter agama dalam proses pembersihan desa Dhukutan di desa Nglurah, Kecamatan Tawangmangu. Dhukutan adalah upacara tradisional penduduk desa Nglurah untuk memperingati hari kematian leluhur mereka yang bernama Kyai Menggung. Upacara tradisional ini diadakan sekali setiap 7 lapan (1 lapan = 35 hari berdasarkan kalender Jawa) Metode yang digunakan untuk menemukan nilai pendidikan karakter agama adalah metode deskriptif kualitatif. Sumber data dalam penelitian ini adalah sesembahan yang terkait dengan pelaksanaan upacara pembersihan desa Dhukutan. Hasil penelitian menunjukkan bahwa nilai-nilai agama yang tercermin dalam upacara tradisional Dhukutan adalah tulus, jujur, patuh, disiplin, rajin berdoa, bersyukur, dan dapat dipercaya. Dalam proses upacara pembersihan desa Dhukutan, ditemukan nilai pendidikan karakter agama yang sangat berguna bagi siswa untuk membentuk kecerdasan intelektual dan emosional siswa. Studi ini menyarankan para pendidik, khususnya di daerah Tawangmangu, untuk menggunakan upacara pembersihan desa Dhukutan sebagai alat pembelajaran pendidikan karakter agama bagi siswa.